Time of Day-Specific Changes in Metabolic Detoxification and Insecticide Tolerance in the House Fly, Musca domestica L. - You, Chunmei; Li, Zelin; Yin, Yuanzhi; Na, Naretuya; Gao, Xiwu (Frontiers in Physiology, 2022)
Both insects and mammals all exhibit a daily fluctuation of susceptibility to chemicals at different times of a day. However, this phenomenon has not been further studied in the housefly (Musca domestica L) and a better understanding of the housefly on chronobiology should be useful for controlling this widespread disease vector. Here we explored diel time-of-day variations in insecticide susceptibility, enzyme activities and xenobiotic-metabolizing enzyme gene expressions. The housefly was most tolerant to beta-cypermethrin in the late photophase at Zeitgeber time (ZT) 8 and 12 (i.e. eight and twelve hours after light is present in the light-dark cycle (LD)). The activities of cytochrome P450, GST, and CarE enzymes were determined in the houseflies collected at various time, indicating that rhythms occur in P450 and CarE activities. Subsequently, we observed diel rhythmic expression levels of detoxifying genes and CYP6D1 and MdαE7 display similar expression patterns with enzyme activities in LD conditions, respectively. No diel rhythm was observed for CYP6D3 expression. These data demonstrated a diel rhythm of metabolic detoxification enzymes and insecticide susceptibility in M. domestica. In the future, the time-of-day insecticide efficacy could be considered into the management of the housefly.